Beyond Likes: The Impact of Social Media Marketing on Healthy Product Repurchase through Brand Image and Trust - Adelia, Winalda; Nuralam, Inggang Perwangsa; Wilopo (Universitas Brawijaya, Indonesia, 2025)
The rapid development of digital technology has reshaped business competition dynamics, especially in the food sector. Social media marketing activities (SMMA) have emerged as strategic tools to engage consumers, build brand image, and foster repurchase intention. This study aims to investigate the influence of Social media marketing activities (SMMA) on repurchase intention, mediated by brand image and brand trust, and moderated by health consciousness. Using a quantitative explanatory approach, data were collected from 280 respondents who had purchased products from PT. Lean Lab Indonesia through TikTok Shop. The sampling method used was purposive sampling. Structural Equation Modeling (SEM-PLS) was employed to analyze the data. The findings indicate that Social media marketing activities (SMMA) significantly influence brand image, brand trust, and repurchase intention. Both brand image and brand trust mediate the relationship between Social media marketing activities (SMMA) and repurchase intention. Furthermore, health consciousness moderates the relationship between brand trust and repurchase intention. The results highlight the importance of integrating health values in digital marketing strategies to boost consumer loyalty in the healthy food industry.